Development a Generic Transaction Processing System Based on Business Process Metadata - Addin Gama Bertaqwa; G.A. Putri Saptawati; Tricya E. Widagdo (Faculty of Computer Science Universitas Indonesia, 2020)
The business processes has a major role in the activities of an organization. Organizations have various types of information systems that support the business processes. One of the systems that support the operations of an organization’s business processes is a transaction processing system that serves to record the daily routine transactions necessary in running a business. In the implementation of business process on information systems, often occur repetitive coding activities for additions or changes to business processes. In general, business process consist of a set of activities and relate to each other between one activity to another. To overcome the problem of repetitive coding implementation, relations between activities must be modelled. In this thesis, business process mapping to data level using metadata approach is proposed as a solution to manage any execution services build on information systems, so that developers can focus to the business process flows. The constructed data model divide building blocks of business process into three type such as event, task and gateway. The data model that has been found capable of storing business process as well as the execution flow of the business process into database. The transaction processing system has been built based on the data model of the process that has been found. Executor of business process has been developed based on metadata that has been designed. From the test results concluded that metadata is able to define business process, and the executor can control the flow of executions of business process correctly. Control of the execution flow of the business process can be done manually by the user or automatically by the executor based on the defined rules in metadata.